Efficiency of Heating and Evaporation of Graphene Nanofluid under Solar Radiation - Tran Quoc Thinh; Dmitriev Alexander; Mikhailova Inna (E3S Web of Conferences, 2024)
The conversion of solar radiation into steam is a crucial focus in today’s green energy, ecology, and clean water production. This study presents the first investigation of the heating and evaporation process of a rotating graphene nanofluid under the influence of solar simulator radiation. The study examined the influence of various factors on the heating and evaporation process of the graphene nanofluid, including the direction of irradiation, graphene concentration and rotation speed. It was demonstrated that the evaporation rate strongly depends on the graphene concentration and the irradiation method of the samples. The heating characteristics of graphene also depend on the irradiation method. It was shown that graphene heated to a higher temperature when in direct contact with radiation, while graphene within the bulk volume was heated less effectively than the base liquid. Moreover, the application of rotating graphene nanofluid in this research was found to enhance thermal efficiency by 2.5% compared to distilled water, with a graphene volume concentration of 0.1%. Consequently, various effects of the rotating graphene nanofluid volume on hydrodynamic, heat, and mass transfer parameters were identified, which hold significance for both fundamental and applied tasks in energy, chemical technology, and ecology.